EFFECT OF MORINGA LEAVES AND VITAMIN C CAPSULE COMBINATIONS IN INCREASEING HEMOGLOBIN LEVELS OF YOUNG WOMEN WITH ANEMIA - Nur Anisa; Sri Wahyuni; Sri Rahayu; Aulia Choirunnisa; Listyaning Eko Martanti (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The prevalence of anemia suffered by girls aged 10-18 years according to the Household Health Survey (SKRT) is 57.1%. The highest contributor of anemia cases in Central Java is Grobogan district, especially in Tanggungharjo Community Health Center, with increasing prevalence of anemia among young women in 2017 from 5.4% to 25.7%. Based on background, researcher wants to determine the effect of Moringa leaf combination dozed 250 mg x 2 / day and vitamin C 50 mg x 2 / day on hemoglobin level changes of young women suffering anemia to decrease anemia in young women Methodology: This quasi experimental research with pretest-posttest control group design involved young women aged 14-19 years suffering anemia. The method of sampling selection was purposive sampling with total 22 respondents assigned as intervention group and other 22 respondent assigned as intervention group. The data analysis used Mann-Whitney test.Results: The average of hemoglobin level in the intervention group increased from 9.37 to 12.10. It proved statistically that there was effect of giving Moringa leaf and vitamin C combination to increase level of hemoglobin of young women suffering anemia. Conclusion: Moringa leaves could significantly increase hemoglobin levels in blood of young women suffering anemia. Raising awareness of anemia and its prevention and treatment among young women should be recommended. Keywords: Anemia, young women, Moringa leaf, Vitamin C, hemoglobin